2018
DOI: 10.1128/msphere.00194-18
|View full text |Cite
|
Sign up to set email alerts
|

Taxon-Driven Functional Shifts Associated with Storm Flow in an Urban Stream Microbial Community

Abstract: Urban streams in various parts of the world are facing increased anthropogenic pressure on their water quality, and storm flow events represent one such source of complex physical, chemical, and biological perturbations. Microorganisms are important components of these streams from both ecological and public health perspectives. Analysis of the effect of perturbations on the stream microbial community can help improve current knowledge on the impact such chronic disturbances can have on these water resources. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 65 publications
8
24
0
1
Order By: Relevance
“…1) and composition (Table S1 , Fig. 3), similar to what we observed previously (Chaudhary et al 2018). The river samples had significantly higher alpha diversity (Shannon) than the effluent samples (nonparametric t-test p= 0.04).…”
Section: Effect Of Uv Disinfection On the River Under Stormflow Condisupporting
confidence: 89%
See 4 more Smart Citations
“…1) and composition (Table S1 , Fig. 3), similar to what we observed previously (Chaudhary et al 2018). The river samples had significantly higher alpha diversity (Shannon) than the effluent samples (nonparametric t-test p= 0.04).…”
Section: Effect Of Uv Disinfection On the River Under Stormflow Condisupporting
confidence: 89%
“…Despite the fact that WWTP effluent accounts for ~70% of the river flow under base conditions in the system we studied, the river is still inhabited by many typical freshwater bacteria such as a variety of Actinobacteria including members of the ac1 clade of actinomycetes, freshwater Pelagibacter, and Polynucleobacter (Hahn et al 2011;Newton et al 2011;Oh et al 2011). We previously observed an increase in the relative abundance of numerous bacteria under stormflow conditions in this system, which coincided with more than double the flow of non-disinfected effluent from the WWTP (Chaudhary et al 2018). Freshwater bacteria made up a greater proportion of the baseflow river community and decreased significantly under actual stormflow conditions (Chaudhary et al 2018), which is what we observed here in the simulated stormflow and baseflow microcosms.…”
Section: A Variety Of Bacteria Survive and Remain Active In Wwtp Efflmentioning
confidence: 70%
See 3 more Smart Citations